ENSO modulates aerobic habitat across varying hypoxia tolerance levels in the Southeast Pacific throughout the twenty-first century - A. Parouffe; B. Dewitte; A. Paulmier; V. Garçon (Scientific Reports)
Abstract The ENSO (El Niño Southern Oscillation), the planet’s most consequential climate mode, imposes significant thermal stress on epipelagic marine ecosystems. However, its effects on aerobic habitats within the epipelagic and mesopelagic zones remain largely uncharted. This study examines these impacts in the Southeast Pacific, a region hosting one of the world’s most pronounced Oxygen Minimum Zones (OMZ), focusing on species with varying hypoxia tolerances. Using Earth System Model simulations, we show that key characteristics of ENSO—its amplitude, spatial and temporal asymmetry referred to as ENSO diversity—significantly affect critical habitats. Specifically, species experience a much greater change in habitat volume during Eastern Pacific (EP) El Niño events compared to Central Pacific (CP) El Niño or La Niña events, despite compensating effects of temperature and oxygen changes on metabolism during the former and the longer duration of the latter. Under future climate conditions, species with low hypoxia tolerance experience the greatest habitat variability, primarily driven by long-term warming-induced habitat loss. By the end of the twenty-first century, El Niño events no longer offset this decline, indicating a diminished capacity of these events to temporarily alleviate climate-related stress.